2009
DOI: 10.1287/orsc.1080.0387
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Entry Knowledge, Learning, and the Survival of New Firms

Abstract: N ew firms are endowed with knowledge and experience at birth through the human capital of their founder(s). Existing empirical research suggests that this pre-entry knowledge and experience will influence the firm's chances of survival; however, the mechanisms underlying this relationship have yet to be investigated. We seek to better understand and unpack this relationship. Specifically, we study the extent to which a founder's pre-entry knowledge of the business activity and pre-entry management experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
244
3
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(261 citation statements)
references
References 98 publications
(131 reference statements)
10
244
3
4
Order By: Relevance
“…This implies it is harder to explain the growth performance of smaller firms, which exhibit greater volatility. This may explain, at least in part, why analyses using relatively large and wellestablished 'new ventures' (Hmieleski and Baron 2009;Dencker et al 2009;Baum and Bird 2010) are able to show higher explanatory power than those included here. Table 4 in 'Appendix' shows this decreasing trend in the explanatory power of our regressions is observed for alternative indicators of goodness of fit-the standard R 2 statistic as well as the Cox-Snell R 2 statistic-for the baseline case.…”
Section: Testing the Hypothesesmentioning
confidence: 85%
See 1 more Smart Citation
“…This implies it is harder to explain the growth performance of smaller firms, which exhibit greater volatility. This may explain, at least in part, why analyses using relatively large and wellestablished 'new ventures' (Hmieleski and Baron 2009;Dencker et al 2009;Baum and Bird 2010) are able to show higher explanatory power than those included here. Table 4 in 'Appendix' shows this decreasing trend in the explanatory power of our regressions is observed for alternative indicators of goodness of fit-the standard R 2 statistic as well as the Cox-Snell R 2 statistic-for the baseline case.…”
Section: Testing the Hypothesesmentioning
confidence: 85%
“…The benefits of greater predictability accrue to business owners, to providers of finance and to governments. For business owners, the value is the availability of a route-map to enable them to plan ahead and check progress over time (Dencker et al 2009). For providers of finance, being able to more accurately estimate the optimal date to provide finance is valuable, because too early an investment may be too risky, whereas delay may mean the opportunity is seized by a rival (Cumming et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a number of studies have found that founders' pre-entry knowledge and experience enhance firms' long-run performance and survival (e.g. Gimeno et al 1997;Aspelund et al 2005;Delmar and Shane 2006;Dencker et al 2009;Geroski et al 2010). Second, the founding teams' human capital characteristics, our independent variables, are individual level variables while USU probability of survival, our dependent variable, is a firm-level variable.…”
Section: Control Variablesmentioning
confidence: 97%
“…This paper was made possible through a research grant from IESE Business School. a firm's strategic direction and its responses to the environment (Furr et al, 2012), which other research in turn has shown to be key determinants of organizational survival chances (Dencker, Gruber, & Shah, 2009;Haveman, 1992). This potential link between the presence of domain experts in strategic decision-making groups, such as corporate boards (Forbes & Milliken, 1999), and organizational survival is important to understand not only because ensuring survival is a critical concern for organizations (Hambrick & D'Aveni, 1992;Mellahi & Wilkinson, 2004) but also because the proportion of domain experts is a readily observable dimension of board composition that organizations can directly influence when creating a board or selecting new directors (see Almandoz, 2012;Pfeffer, 1972).…”
mentioning
confidence: 99%